DEVELOPMENT OF A MATHEMATICAL MODEL OF THE DRIVE WITH LINEAR SYNCHRONOUS MOTOR FOR RESEARCH OF TRANSIENTS - Zaitsev, O. M.; Voskoboinyk, V. E.; Komarov, S. V.; Voroshylov, O. S. (Science and Transport Progress, 2004)
The variant of mathematical model of the linear synchronous electric drive which allows to take into account features of a design and a ratio of parameters is offered. The model allows to investigate electromechanical and thermal processes in the linear electric drive with synchronous motor.